Enhancing The Security of Wireless Communication Systems: A Path Towards Global Protection - Rajkumar Garg, Upasana Singh (Journal of Informatics Education and Research, 2024)
Wireless communication systems have been around since the early 19th century. Scottish scientist James Clerk Maxwell laid the foundation for the theory of electromagnetic waves in 1837, which showed that it was possible to transmit information through the air without wires. Guglielmo Marconi developed the first practical wireless communication system in the late 19th century, which used radio waves to transmit Morse code signals. Since then, a number of uses for wireless communication systems have emerged, including point-to-point and ship-to-shore communication. Enhanced security in wireless communication systems offers a multitude of benefits, including the protection of users' privacy, increased availability, improved reliability, reduced risk of fraud, and compliance with regulations. By implementing advanced security measures, unauthorized parties find it more challenging to eavesdrop on communications, ensuring the privacy of users. Robust encryption, authentication, and access control methods contribute to this protection. It measures protect wireless communication systems from DoS attacks by filtering out malicious traffic and limiting connections, ensuring consistent availability for legitimate users. These measures also prevent data interception, modification, and theft through MitM attacks. Strong encryption and authentication mechanisms guarantee the integrity of communications, enhancing the reliability of wireless systems. It monitors minimizes the risk of fraud by making it harder for unauthorized individuals to access sensitive personal information such as credit card numbers and passwords. Robust security includes strong authentication methods, data encryption, and the use of fraud detection systems, protecting individuals and businesses from fraudulent activities. This study offers a thorough framework for increasing wireless communication system security and achieving global protection. For the security and integrity of data during transmission, strong encryption algorithms are essential. Advanced techniques, like quantum cryptography, offer unbreakable encryption based on quantum mechanics. Adopting quantum-resistant algorithms provides long-term security against emerging threats. Robust encryption algorithms, such as quantum cryptography, protect data confidentiality and integrity. Quantum-resistant algorithms ensure long-term security against emerging threats. Unauthorised access and impersonation risk are decreased by robust authentication systems, such as multi-factor and biometric techniques. Effective intrusion detection systems quickly detect and address possible threats thanks to machine learning and AI. Wireless communication network security is further increased through anomaly-based detection and real-time threat intelligence.